Draft Annual Plan 1986-87 Maharashtra State Part II - Planning Commission (Planning Commission, 1986)
Seventh Five Year Plan 1983-90 Statement showing outlays on Abstract Statement showing sub-sectorwise outlay and expenditure Special Component Plan for Scheduled Castes and Nov-buddhas- 1986-87in Maharashtra State sector and sub-sector-wise-Outlay. Draft Annual Plan, 1986-87-Head of Development States/Union Territories-Outlay and Expenditure Detailed Statement of schemes included Outlay for removal of regional backlog.
Government of Maharashtra Planning Department